Influences of resolvin D1 and D2 on the risk of type 2 diabetes mellitus: a Chinese community-based cohort study - Sun, Qian; Wang, Junrong; Jing, Yang; Liu, Jingchao; Jin, Jianrong; Wang, Sudan; Zhang, Jin; Liu, Kaili; Chen, Xiaofang; Zhou, Hui; Dong, Chen (Frontiers in Immunology, 2023)
Background Although cellular and animal studies have reported that resolvin D1 (RvD1) and resolvin D2 (RvD2) are mechanisms involved in the development of type 2 diabetes mellitus (T2DM), the impact of RvD1 and RvD2 on the risk of T2DM at the population level remains unclear. Methods We included 2755 non-diabetic adults from a community-based cohort in China and followed for seven years. Cox proportional hazards model was used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for the association of RvD1 and RvD2 with T2DM probability. Time-dependent receiver operator characteristics (ROC) curve was used to evaluate the predictive performance of RvD1 and RvD2 for the risk of T2DM based on the Chinese CDC T2DM prediction model (CDRS). Results In total, 172 newly developed T2DM cases were identified. Multivariate-adjusted HRs (95% CI) for T2DM across quartiles of RvD1 levels (Q1, Q2, Q3 and Q4) were 1.00, 1.64 (1.03-2.63), 1.80 (1.13-2.86) and 1.61 (1.01-2.57), respectively. Moreover, body mass index (BMI) exhibited a significant effect modification in the association of RvD1 with incident T2DM (Pinteraction = 0.026). After multivariate adjustment, the HR (95% CI) for T2DM in the fourth compared with the first quartile of RvD2 was 1.94 (95% CI: 1.24-3.03). Time-dependent ROC analysis showed that the area under time-dependent ROC curves of the “CDRS+RvD1+RvD2” model for the 3-, 5- and 7-year risk of T2DM was 0.842, 0.835 and 0.828, respectively. Conclusions Higher RvD1 and RvD2 levels are associated with a higher risk of T2DM at the population level.